PARDOS: An Educational Software Tool for the Analysis of Sound Propagation - Domingo Pardo-Quiles; Jose-Victor Rodriguez; Ignacio Rodriguez-Rodriguez (IEEE Access, 2020)
The educational software tool PARDOS is presented for the analysis of sound propagation, being applicable for supplementing and enhancing the understanding and learning of the principles of acoustic engineering thanks to the features it offers. With this tool, students (high school or undergraduate as well as Ph.D.) will be able to create environments - multi-modeled obstacles - and settings based on real scenarios, load acoustic sources, simulate the expected insertion losses (IL) and acoustic attenuation at any receiver (listener) location, or use the auralization module to test the acoustic quality of the design carried out. Moreover, the learning of the fundamentals of acoustic propagation is supported by a set of four guided practices embedded in the software application, which can also be very useful for teachers. The main advantage of the presented tool is that, unlike most of the computationally demanding alternatives for acoustic propagation - which usually imply complex CAD files, and highly dense raytracing approaches - PARDOS is a user-friendly teaching-oriented software developed with MATLAB that successfully combines the use of the Uniform Theory of Diffraction (UTD), Image Source (IS) method, graph theory, funicular polygons, and Fresnel ellipsoids to obtain high accuracy performances while significantly lowering computational requirements. Moreover, the design of any obstacle can easily be achieved using the proper combination of wedges, rectangles, cylinders, and T/Y-shaped structures.